The correlation between demography and clinical status based on WHO staging in MSM HIV patients at Bali Medical Centre - Dhanesh Sukumar Nair; I Nyoman Sutarsa; A A Sagung Sawitri; Komang Ayu Kartika Sari (Intisari Sains Medis, 2019)
Background: HIV stands for human immunodeficiency virus which is in the category of lentivirus (a subgroup of retrovirus) that causes HIV infection and can lead to acquired immunodeficiency syndrome (AIDS).Â  HIV affects specific cells of the immune system, called CD4 cells, or T cells. Over time, if left untreated, HIV can destroy so many of these cells that the body would not be able to fight off infections and disease. However, with proper medical care, HIV can be controlled. Treatment for HIV is called antiretroviral therapy (ART). It involves taking a combination of HIV medicines (called an HIV regimen) every day. Today, a person who diagnosed with HIV before the disease is far advanced and who gets and stays on ART can live a nearly normal lifespan.Aim: This study aims to investigate and analyze the predictors that influence WHO staging of homosexual MSM HIV patients treated at the BMC hospital in Bali. Indonesia, and to determine the factors that lead to differences in the WHO staging in MSM patients with HIV.Method: This study used a retrospective cohort method using secondary data from BMC Hospital. The sample population for this research is MSM HIV patients treated at the BMC hospital in Bali. Using the total sampling method yielded 271 samples.Result and Conclusion: the HIV incidence is a serious matter in Indonesia. One of the underlying factors for the delayed diagnosis of HIV is the lack of knowledge about the improved prognosis of early ARV treatment and a fear of being stigmatized by the community. Increased availability of HIV testing at hospitals, combined with enhanced knowledge of the prognosis of HIV treatment among crucial affected population, and the community at large and may improve earlier testing.